An Update on SGLT2 Inhibitors for the Treatment of Diabetes Mellitus - Hsia, Daniel S (Curr Opin Endocrinol Diabetes Obes, 2017)
PURPOSE OF REVIEW: SGLT2 inhibitors are the newest class of oral anti-hyperglycemic agents that have been approved for the treatment of diabetes mellitus. Over the past year there have been significant developments in both the safety and efficacy of this class of medications that are presented in this review. RECENT FINDINGS: Besides data on the glucose lowering effect of SGLT2 inhibitors, other metabolic benefits have been demonstrated for this class of medications. Moreover, there have been 3 FDA Drug Safety Communications issued in 2015 that have led to additional drug labeling. The basic mechanism of action, indications, glucose-lowering benefits, other metabolic benefits, and adverse side effects of SGLT2 inhibitors are presented in this review. SUMMARY: SGLT2 inhibitors are medications that have a unique mechanism of action and that lower glucose independent of insulin. Given the recent findings on efficacy and benefits, these agents are rapidly establishing their role in the treatment of diabetes. Especially in patients with type 2 diabetes not willing or not ready to start insulin, SGLT2 inhibitors may be another option in those patients requiring additional glucose lowering and in those with acceptable risk factor profiles. Although there appears to be some positive benefits in cardiovascular endpoints, more research on the long term outcomes in people taking SGLT2 inhibitors is warranted.